Friction Coefficient and Compression Behavior of Particle Reinforced Aluminium Matrix Composites - Ugur Α.; Gokkaya, H.; Sur, G.; Eltugral, N. (Engineering, Technology & Applied Science Research, 2019)
Metal matrix composites (MMCs) are materials used in a large range of engineering applications. In this paper, the relatively low-cost stir casting is evaluated with the use for Silisyum Carbite (SiC) as reinforcement and Al7075 alloy as matrix to produce MMCs with varied reinforcement from 10% to 18%. The produced composites were examined, and their wear behavior was investigated. The results showed that the mechanical properties of the MMCs decrease with the increase of the mass percentage of reinforcement and compression.